A preparation method of Fe-Cu-C-lubricating component gradient composite antifriction material and corresponding materials

Cu-coated Fe composite powders were prepared by electroless plating and combined with casting forming process, Fe-Cu-C-lubricating component gradient composite friction reduction materials were prepared, which solved the problem of insufficient mechanical and friction reduction performance of existing iron-based friction reduction materials under high temperature, high speed and heavy load conditions, and achieved high strength support and good friction reduction performance.

CN116422888BActive Publication Date: 2025-03-25HEFEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310412319.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2025-03-25
Estimated Expiration
2043-04-18

AI Technical Summary

Technical Problem

The existing iron-based friction-reducing materials have insufficient mechanical properties and friction-reducing properties under high temperature, high speed and heavy load conditions. The preparation process is complex and costly, making it difficult to meet the dimensional accuracy requirements under complex working conditions.

Method used

Cu-coated Fe composite powder was prepared by electroless plating, and Fe-Cu-C slurry was prepared by casting forming process to form a layered composite green body, and pressure-free sintering was performed in a hydrogen atmosphere, and finally oil-immersion or melt-wet lubrication treatment was performed to prepare Fe-Cu-C-lubricating component gradient composite friction reducing material.

Benefits of technology

It improves the structural uniformity and mechanical properties of the material, reduces material defects, broadens the scope of use of the material, and achieves good friction reduction performance and high-strength support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116422888B_ABST
    Figure CN116422888B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of composite materials, and to a preparation method and corresponding materials of a Fe-Cu-C-lubricating component gradient composite antifriction material. The method of the present invention comprises: preparing Cu-coated Fe powder by chemical plating, preparing bottom Fe-Cu-C slurry and multilayer Fe-Cu-C slurry of different compositions by ball milling treatment and vacuum defoaming treatment, taking bottom Fe-Cu-C slurry and multilayer Fe-Cu-C slurry as raw materials, respectively obtaining bottom green body and multilayer green body by casting, drying and curing treatment, matching bottom green body and multilayer green body, and obtaining layered composite green body by molding treatment, performing debinding treatment on the obtained layered composite green body in a hydrogen atmosphere, and performing pressureless sintering in a hydrogen atmosphere, obtaining Fe-Cu-C-pore gradient porous sintered body and performing oil immersion treatment or melt-immersion solid lubricant treatment, and obtaining Fe-Cu-C-lubricating component gradient composite antifriction material. The composite antifriction material prepared by the present invention has both high-strength support and good antifriction performance, and widens the scope of use of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a preparation method of a Fe-Cu-C-lubricating component gradient composite antifriction material and corresponding materials. Background Art

[0002] Iron-based oil-containing materials have good self-lubricating properties, fatigue resistance, high strength and other mechanical properties and are inexpensive, making them one of the most widely used powder metallurgy anti-friction materials. With the development of modern industry, the mechanical properties and anti-friction properties of iron-based oil-containing materials are insufficient when dealing with complex working conditions such as high temperature, high speed and heavy load.

[0003] At present, preparing multi-layer powder metallurgy materials is one of the main ways to improve the comprehensive mechanical and tribological properties of sintered iron-based anti-friction materials. After the materials are mixed, they are loaded into a mold, and a multi-layer iron-based powder metallurgy green sample is pressed by a process of two powder spreading and one pressing. The multi-layer sample after the green sample is sintered is vacuum oiled and ground to become a friction sample. In the actual preparation process, when preparing complex parts, it is necessary to design and equip complex molds, which is not conducive to the production of larger-sized materials. At the same time, the complex process operation is not conducive to automated production, and the production cost is high. The Chinese patent with publication number CN105817605A discloses a functionally gradient wear-resistant iron-based composite material and a preparation method thereof. The material is composed of a parent metal and a plurality of conical reinforcements. A conical preform is prepared by vacuum sintering, and then a functionally gradient wear-resistant iron-based composite material is obtained by casting. However, the forming cycle of gradient iron-based composite materials prepared by casting forming process is long, and the dimensional accuracy of casting forming samples is poor. They need to undergo subsequent fine processing before they can be used, which limits the use of materials in complex working conditions with high requirements for dimensional accuracy. At the same time, there is also waste of raw materials in the preparation process, and production costs increase.

[0004] Tape casting is a commonly used method for forming ceramic products. It prepares a uniformly dispersed stable slurry and flows it down in the container barrel of the tape casting machine. It is scraped and coated on a special base belt with a certain thickness. After drying and curing, it is peeled off to form a film of a green tape. Then, according to the size and shape of the finished product, the green tape is punched, laminated and processed to form a blank product to be sintered. It has the advantages of fast speed, high degree of automation and high efficiency. However, the tape casting process is mainly used in the field of ceramic materials, and requires that the particle size of the raw material powder should not be too large, and the raw material powder must form a uniform and stable suspension slurry when mixed with a dispersant, a binder and a plasticizer in a solvent. For iron-based anti-friction materials, the tape casting process is used to prepare anti-friction materials. Due to the large difference in the particle size of iron powder, copper powder and graphite powder, and the wide density range between the raw material powders, it is not easy to form a suspension slurry when preparing the tape casting slurry. These all limit the use of the tape casting process in the field of iron-based anti-friction materials.

[0005] Therefore, how to improve the preparation efficiency of iron-based anti-friction materials and at the same time make the multi-layer gradient iron-based anti-friction materials have higher mechanical properties and self-lubricating properties is an urgent problem to be solved. Summary of the invention

[0006] In view of this, in order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a Fe-Cu-C-lubricating component gradient composite antifriction material.

[0007] According to one aspect of the present invention, the present invention provides a method for preparing a Fe-Cu-C-lubricating component gradient composite antifriction material, comprising:

[0008] Step 1: Preparation of Cu-coated Fe powder

[0009] A chemical plating solution is prepared using copper sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water, iron powder is plated using the prepared chemical plating solution under constant temperature conditions, and the composite powder obtained by the plating is reduced to obtain Cu-coated Fe composite powders with different coating ratios;

[0010] Step 2: Preparation of Fe-Cu-C slurries with different compositions

[0011] A first coating ratio of Cu-coated Fe composite powder and graphite powder is used to prepare a base material, and a second coating ratio of Cu-coated Fe composite powder, graphite powder and a pore-forming agent is used to prepare a composite material.

[0012] The bottom layer raw material and the multi-layer raw material are respectively subjected to ball milling treatment to obtain a bottom layer tape casting slurry and a multi-layer tape casting slurry, respectively; the bottom layer tape casting slurry and the multi-layer tape casting slurry are respectively subjected to vacuum defoaming treatment to obtain a bottom layer Fe-Cu-C slurry and a multi-layer Fe-Cu-C slurry;

[0013] Step 3: Preparation of layered composite green body

[0014] The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry are used as raw materials respectively, and the bottom green body and the multi-layer green body are obtained by casting, drying and curing. After the bottom green body and the multi-layer green body are matched, a layered composite green body is obtained by molding.

[0015] Step 4: Preparation of Fe-Cu-C-pore gradient porous sintered body

[0016] The layered composite green body obtained in step 3 is subjected to a binder removal treatment in a hydrogen atmosphere, and is pressurelessly sintered in a hydrogen atmosphere to obtain a Fe-Cu-C-pore gradient porous sintered body;

[0017] Step 5: Post-treatment of Fe-Cu-C-pore gradient porous sintered body

[0018] The Fe-Cu-C-pore gradient porous sintered body obtained in step 4 is subjected to oil immersion treatment or melt-immersion solid lubricant treatment to obtain a Fe-Cu-C-lubricating component gradient composite anti-friction material.

[0019] According to an exemplary embodiment of the present invention, step 1 of the method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material of the present invention comprises:

[0020] A chemical plating solution is prepared by using copper sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water in a mass ratio of 1:2.7:0.7:0.002:1.8:50;

[0021] A constant temperature water bath is used to keep a certain mass of chemical plating solution at 62.5° C. and ultrasonically stir it, and iron powder is added to the chemical plating solution, wherein the mass ratio of copper sulfate pentahydrate to iron powder in the chemical plating solution is 1:1-1:2.25, and a 10wt% sodium hydroxide solution is added dropwise to the chemical plating solution containing the iron powder, and the pH value is adjusted to 12.5 and then the addition is stopped, and the temperature is kept and ultrasonically stirred for 60 minutes, and the supernatant in the solution system is washed and replaced with deionized water every 6 hours, and the obtained composite powder is placed at 80-90° C. and dried for 12-24 hours to obtain a dry composite powder;

[0022] The dried composite powder is placed in a hydrogen atmosphere at 300-400° C. for reduction for 1-2 hours to obtain Cu-coated Fe composite powders with different coating ratios.

[0023] According to an exemplary embodiment of the present invention, step 2 of the method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material of the present invention comprises:

[0024] A base material is prepared by using a Cu-coated Fe composite powder and graphite powder in a first coating ratio, wherein the content of the graphite powder is 0.6-1.0wt%, and the mass ratio of Cu to Fe in the Cu-coated Fe composite powder in the first coating ratio is 1:5.25 to 1:9;

[0025] A composite raw material is prepared by using a Cu-coated Fe composite powder, graphite powder and a pore former in a second coating ratio, wherein the content of the graphite powder is 0.6-1.0wt%, the content of the pore former is 5-10wt%, the mass ratio of Cu to Fe in the Cu-coated Fe composite powder in the second coating ratio is 1:4 to 1:9, and the pore former powder is ammonium bicarbonate or soluble starch or a mixture of ammonium bicarbonate and soluble starch in equal proportions;

[0026] The bottom layer raw material and the multi-layer raw material are respectively subjected to ball milling treatment to obtain a bottom layer casting slurry and a multi-layer casting slurry, and the obtained bottom layer casting slurry and the multi-layer casting slurry are respectively subjected to vacuum defoaming treatment to obtain a bottom layer Fe-Cu-C slurry and a multi-layer Fe-Cu-C slurry.

[0027] According to an exemplary embodiment of the present invention, in step 2 of the method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material of the present invention, the bottom raw material and the multi-layer raw material are respectively subjected to ball milling treatment to obtain a bottom casting slurry and a multi-layer casting slurry, respectively, and the obtained bottom casting slurry and multi-layer casting slurry are respectively subjected to vacuum defoaming treatment, including:

[0028] The bottom raw material and the multi-layer raw material are respectively ball-milled at a speed of 400 r / min for 6-18 hours using a dispersant, a binder, a plasticizer and anhydrous ethanol as ball milling auxiliary materials to obtain a bottom casting slurry and a multi-layer casting slurry, wherein the mass ratio of the dispersant, the binder, the plasticizer to the bottom raw material or the multi-layer raw material is 1:2:1:100, and the mass ratio of the anhydrous ethanol to the bottom raw material or the multi-layer raw material is 1:1 to 1:2;

[0029] Defoaming agents were added to the bottom casting slurry and the multi-layer casting slurry respectively, and the slurries were placed in a vacuum environment for defoaming to obtain Fe-Cu-C slurries with different compositions, wherein the mass ratio of the total mass of the defoaming agent to the bottom raw material or the multi-layer raw material was 1:100 to 1:50.

[0030] According to an exemplary embodiment of the present invention, in step 2 of the method for preparing the Fe-Cu-C-lubricating component gradient composite anti-friction material of the present invention, the dispersant is polyethylene glycol or triethanolamine, the binder is polyvinyl butyral or phenolic resin, the plasticizer is phthalates or dibutyl phthalate, and the defoamer is one or more of cyclohexanone, dimethyl silicone oil or oleic acid. When the defoamer is composed of two or more of cyclohexanone, dimethyl silicone oil or oleic acid, the components of the defoamer are mixed in equal proportions.

[0031] According to an exemplary embodiment of the present invention, step three of the method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material of the present invention comprises:

[0032] The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry are used as raw materials respectively, and the bottom green body and the multi-layer green body are obtained respectively by tape casting and drying and solidification treatment, wherein the drying and solidification treatment temperature is 25-30° C. and the drying and solidification time is 24-48 hours;

[0033] After matching the bottom green body and the multi-layer green body, the green body is kept under a static pressure of 200 MPa for 5 minutes to obtain a layered composite green body, wherein the thickness of the matched bottom green body and the multi-layer green body is 1:0.5 to 1:2.

[0034] According to an exemplary embodiment of the present invention, step 4 of the method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material of the present invention comprises:

[0035] The layered composite green body obtained in step 3 is placed in a hydrogen atmosphere, heated to 300-350°C at a heating rate of 1°C / min, and kept warm for 5-7h, and then heated to 480-520°C at a heating rate of 3°C / min, and kept warm for 0.5-1.5h to obtain a layered composite green body after binder removal treatment;

[0036] The debinding-treated layered composite green body is placed in a hydrogen atmosphere, heated to 1080-1180°C at a heating rate of 5°C / min, and kept warm for 1-2 hours to obtain a Fe-Cu-C-pore gradient porous sintered body.

[0037] According to an exemplary embodiment of the present invention, in step five of the method for preparing the Fe-Cu-C-lubricating component gradient composite anti-friction material of the present invention, the oil immersion treatment includes: heating the mechanical oil to 80-90°C in a constant temperature water bath and immersing the Fe-Cu-C-pore gradient porous sintered body in the insulating mechanical oil for 2-6 hours.

[0038] According to an exemplary embodiment of the present invention, in step five of the method for preparing the Fe-Cu-C-lubricating component gradient composite anti-friction material of the present invention, the melt infiltration solid lubricant treatment includes: heating the solid lubricant polytetrafluoroethylene to 320-340°C to obtain molten polytetrafluoroethylene, placing the Fe-Cu-C-pore gradient porous sintered body in molten polytetrafluoroethylene for melt infiltration treatment for 2-4 hours, and cooling to room temperature.

[0039] On the other hand, the present invention provides a Fe-Cu-C-lubricating component gradient composite antifriction material, and the Fe-Cu-C-lubricating component gradient composite antifriction material is prepared according to the above method.

[0040] The preparation method of the Fe-Cu-C-lubricating component gradient composite antifriction material and the corresponding material of the present invention have the following beneficial effects:

[0041] 1. The alloy material is prepared by using the composite powder prepared by chemical plating as the raw material, so that the copper and iron alloy elements are dispersed more evenly, thereby improving the uniformity of the material's organization.

[0042] 2. The green specimen is prepared by tape casting process, and the pores formed are more uniform, which reduces the material defects caused by more pores in a certain area, thereby improving the mechanical properties of the material.

[0043] 3. The tape casting process is used to prepare green samples, avoiding the shortcomings of the traditional method of preparing composite materials due to size limitations and broadening the scope of use of the material.

[0044] 4. The Fe-Cu-C-lubricating component gradient composite anti-friction material prepared by the present invention using a tape casting process and a powder metallurgy process has a high-strength support body, and the anti-friction layer has good anti-friction performance due to the high lubricant content. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 A flow chart of a method for preparing a Fe-Cu-C-lubricating component gradient composite antifriction material according to exemplary embodiments 1-5 of the present invention;

[0047] Figure 2 A scanning electron microscope (SEM) photograph of the fracture surface of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared for exemplary embodiment 1 of the present invention before oil immersion treatment;

[0048] Figure 3 A cross-sectional scanning electron microscope (SEM) photograph of a Fe-Cu-C-lubricating component gradient composite antifriction material before oil immersion treatment is prepared for exemplary embodiment 2 of the present invention;

[0049] Figure 4 A cross-sectional scanning electron microscope (SEM) photograph of a Fe-Cu-C-lubricating component gradient composite antifriction material before oil immersion treatment is prepared for exemplary embodiment 3 of the present invention;

[0050] Figure 5A scanning electron microscope (SEM) photograph of the fracture surface of the Fe-Cu-C-lubricating component gradient composite antifriction material before melt infiltration is prepared for exemplary embodiment 4 of the present invention;

[0051] Figure 6 Friction coefficient curves at room temperature of Fe-Cu-C-lubricating component gradient composite anti-friction materials prepared for exemplary embodiments 1 to 5 of the present invention. DETAILED DESCRIPTION

[0052] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0053] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.

[0054] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.

[0055] Figure 1 The process flow chart of the preparation method of the Fe-Cu-C-lubricating component gradient composite antifriction material of the present invention is as follows: Figure 1 The process flow shown is a detailed description of the preparation method of the Fe-Cu-C-lubricating component gradient composite anti-friction material of the present invention.

[0056] Example 1

[0057] Step 1: Preparation of Cu-coated Fe powder

[0058] A chemical plating solution was prepared with copper sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water in a mass ratio of 1:2.7:0.7:0.002:1.8:50. A constant temperature water bath was used to maintain a constant temperature of 62.5°C and ultrasonic stirring was performed. 2.25 parts by mass of copper sulfate pentahydrate and 1.0 parts by mass of iron powder were added to the chemical plating solution respectively. A 10wt% sodium hydroxide solution was continuously added to the chemical plating solution containing iron powder, and the pH value was adjusted to 12. 5, the dropping was stopped, and the solution system containing the plated composite powder was obtained after continuous heat preservation and ultrasonic stirring for 60 minutes. The supernatant in the solution system was washed and replaced with deionized water every 6 hours, and the obtained composite powder was placed at 85°C for 18 hours to obtain a dry composite powder; the dried composite powder was placed in a hydrogen atmosphere at 350°C for reduction for 1.5 hours to obtain a composite powder of 1 part by weight of Cu coated with 9 parts by weight of Fe and a composite powder of 1 part by weight of Cu coated with 4 parts by weight of Fe, respectively;

[0059] Step 2: Preparation of Fe-Cu-C slurries with different compositions

[0060] A bottom layer raw material is prepared by coating 9 parts by weight of Fe composite powder with 0.8wt% graphite powder and 1 part by weight of Cu as the balance in a first coating ratio, and a double layer raw material is prepared by coating 4 parts by weight of Fe composite powder with 0.8wt% graphite powder, 10wt% pore-forming agent soluble starch and 1 part by weight of Cu as the balance in a second coating ratio;

[0061] Weigh dispersant polyethylene glycol, adhesive polyvinyl butyrate, plasticizer dibutyl phthalate, bottom raw material or multi-layer raw material and anhydrous ethanol in a mass ratio of 1:2:1:100:100, ball-mill the bottom raw material and the multi-layer raw material at a speed of 400 r / min for 12 h to obtain bottom casting slurry and multi-layer casting slurry, respectively, add 2% defoaming agent dimethyl silicone oil to the bottom casting slurry and the multi-layer casting slurry, respectively, place them in a vacuum environment for defoaming, and obtain bottom Fe-Cu-C slurry and multi-layer Fe-Cu-C slurry, respectively;

[0062] Step 3: Preparation of layered composite green body

[0063] The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry were used as raw materials, respectively, by tape casting, drying and curing at 30°C for 24 hours and 36 hours, respectively, to obtain the bottom green body and the multi-layer green body, respectively, and the bottom green body and the multi-layer green body were matched with each other in thickness of 1:0.5, and then subjected to a molding treatment of holding the pressure at a static pressure of 200 MPa for 5 minutes to obtain a layered composite green body;

[0064] Step 4: Preparation of Fe-Cu-C-pore gradient porous sintered body

[0065] The layered composite green body obtained in step 3 is placed in a hydrogen atmosphere, heated to 300°C at a heating rate of 1°C / min, kept warm for 7 hours, and then heated to 500°C at a heating rate of 3°C / min, kept warm for 1.0 hour to obtain a layered composite green body after binder removal treatment; then the layered composite green body after binder removal treatment is placed in a hydrogen atmosphere, heated to 1130°C at a heating rate of 5°C / min, and kept warm for 1.5 hours to obtain a Fe-Cu-C-pore gradient porous sintered body;

[0066] Step 5: Post-treatment of Fe-Cu-C-pore gradient porous sintered body

[0067] The mechanical oil is heated to 85°C in a constant temperature water bath and kept warm. The Fe-Cu-C pore gradient porous sintered body obtained in step 4 is immersed in the warm mechanical oil for 4 hours to obtain a Fe-Cu-C lubricating component gradient composite anti-friction material.

[0068] Example 2

[0069] Step 1: Preparation of Cu-coated Fe powder

[0070] A chemical plating solution was prepared with copper sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water in a mass ratio of 1:2.7:0.7:0.002:1.8:50. A constant temperature water bath was used to maintain a constant temperature at 62.5°C and ultrasonic stirring was performed. 1.32 parts by mass of sulfuric acid pentahydrate and 2.25 parts by mass of iron powder of copper sulfate pentahydrate were added to the chemical plating solution respectively. A 10 wt % sodium hydroxide solution was continuously added to the chemical plating solution containing the iron powder. After the pH value was adjusted to 12.5, Stop dripping, keep warm and stir ultrasonically for 60 minutes to obtain a solution system containing plated composite powders, wash and replace the supernatant in the solution system with deionized water every 6 hours, dry the obtained composite powder at 80°C for 24 hours to obtain a dry composite powder; reduce the dried composite powder at 400°C in a hydrogen atmosphere for 1.0 hour to obtain composite powders of 1 part by weight of Cu coated with 5.25 parts by weight of Fe and 1 part by weight of Cu coated with 9 parts by weight of Fe, respectively;

[0071] Step 2: Preparation of Fe-Cu-C slurries with different compositions

[0072] A bottom layer material is prepared by coating 5.25 parts by weight of Fe composite powder with 1.0 wt% graphite powder and the balance of 1 part by weight of Cu in a first coating ratio, and a double layer material is prepared by coating 9 parts by weight of Fe composite powder with 0.8 wt% graphite powder, 5 wt% pore former ammonium bicarbonate powder and the balance of 1 part by weight of Cu in a second coating ratio;

[0073] Weigh dispersant triethanolamine, adhesive phenolic resin, plasticizer di(2-ethylhexyl) phthalate, bottom raw material or multi-layer raw material and anhydrous ethanol in a mass ratio of 1:2:1:100:50, ball-mill the bottom raw material and the multi-layer raw material at a speed of 400 r / min for 6 hours to obtain bottom casting slurry and multi-layer casting slurry, respectively, add 2% defoaming agent cyclohexanone and dimethyl silicone oil (the mass ratio of cyclohexanone to dimethyl silicone oil is 1:1) to the bottom casting slurry and the multi-layer casting slurry, respectively, place them in a vacuum environment for defoaming, and obtain bottom Fe-Cu-C slurry and multi-layer Fe-Cu-C slurry, respectively;

[0074] Step 3: Preparation of layered composite green body

[0075] The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry were used as raw materials, respectively, by tape casting, drying and curing at 25°C for 48 hours and 24 hours, respectively, to obtain the bottom green body and the multi-layer green body, respectively, and the bottom green body and the multi-layer green body were matched with each other in thickness of 1:2, and then subjected to a molding treatment of holding the pressure at a static pressure of 200 MPa for 5 minutes to obtain a layered composite green body;

[0076] Step 4: Preparation of Fe-Cu-C-pore gradient porous sintered body

[0077] The layered composite green body obtained in step 3 is placed in a hydrogen atmosphere, heated to 350°C at a heating rate of 1°C / min, kept warm for 5 hours, and heated to 480°C at a heating rate of 3°C / min, kept warm for 1.5 hours to obtain a layered composite green body after binder removal treatment; then the layered composite green body after binder removal treatment is placed in a hydrogen atmosphere, heated to 1080°C at a heating rate of 5°C / min, kept warm for 2.0 hours, and a Fe-Cu-C-pore gradient porous sintered body is obtained;

[0078] Step 5: Post-treatment of Fe-Cu-C-pore gradient porous sintered body

[0079] The mechanical oil is heated to 90°C in a constant temperature water bath and kept warm. The Fe-Cu-C pore gradient porous sintered body obtained in step 4 is immersed in the warm mechanical oil for 2 hours to obtain a Fe-Cu-C lubricating component gradient composite anti-friction material.

[0080] Example 3

[0081] Step 1: Preparation of Cu-coated Fe powder

[0082] A chemical plating solution was prepared with copper sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water in a mass ratio of 1:2.7:0.7:0.002:1.8:50. A constant temperature water bath was used to maintain a constant temperature at 62.5°C and ultrasonic stirring was performed. 1.83 parts by mass of copper sulfate pentahydrate and 1.42 parts by mass of copper sulfate pentahydrate were added to the chemical plating solution respectively. A 10 wt % sodium hydroxide solution was continuously added to the chemical plating solution containing the iron powder. After the pH value was adjusted to 12.5, Stop dripping, keep warm and ultrasonically stir for 60 minutes to obtain a solution system containing plated composite powders, wash and replace the supernatant in the solution system with deionized water every 6 hours, dry the obtained composite powder at 90°C for 18 hours to obtain a dry composite powder; reduce the dried composite powder in a hydrogen atmosphere at 300°C for 2.0 hours to obtain composite powders of 1 part by weight of Cu coated with 7.33 parts by weight of Fe and 1 part by weight of Cu coated with 5.67 parts by weight of Fe, respectively;

[0083] Step 2: Preparation of Fe-Cu-C slurries with different compositions

[0084] A bottom layer raw material is prepared by coating 7.33 parts by weight of Fe composite powder with 0.6wt% graphite powder and 1 part by weight of Cu as the balance in a first coating ratio, and a double layer raw material is prepared by coating 5.67 parts by weight of Fe composite powder with 1.0wt% graphite powder, 8wt% pore-forming agent ammonium bicarbonate and soluble starch (ammonium bicarbonate: soluble starch is 1:1) and 1 part by weight of Cu as the balance in a second coating ratio;

[0085] Weighing a dispersant polyethylene glycol, an adhesive phenolic resin, a plasticizer di(2-ethylhexyl) phthalate, a bottom raw material or a multi-layer raw material and anhydrous ethanol in a mass ratio of 1:2:1:100:75, respectively subjecting the bottom raw material and the multi-layer raw material to ball milling at a speed of 400 r / min for 18 h to obtain a bottom casting slurry and a multi-layer casting slurry, respectively, adding 1% of a defoaming agent oleic acid to the bottom casting slurry and the multi-layer casting slurry, respectively, placing them in a vacuum environment for defoaming, and respectively obtaining a bottom Fe-Cu-C slurry and a multi-layer Fe-Cu-C slurry;

[0086] Step 3: Preparation of layered composite green body

[0087] The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry were used as raw materials, respectively, by tape casting, drying and curing at 30°C for 48 hours and 36 hours, respectively, to obtain the bottom green body and the multi-layer green body, respectively, and the bottom green body and the multi-layer green body were matched with each other in thickness of 1:1, and then subjected to a molding treatment of holding the pressure at a static pressure of 200 MPa for 5 minutes to obtain a layered composite green body;

[0088] Step 4: Preparation of Fe-Cu-C-pore gradient porous sintered body

[0089] The layered composite green body obtained in step 3 is placed in a hydrogen atmosphere, heated to 350°C at a heating rate of 1°C / min, kept warm for 6 hours, and then heated to 520°C at a heating rate of 3°C / min, kept warm for 0.5 hours to obtain a layered composite green body after binder removal treatment; then the layered composite green body after binder removal treatment is placed in a hydrogen atmosphere, heated to 1180°C at a heating rate of 5°C / min, and kept warm for 1.0 hours to obtain a Fe-Cu-C-pore gradient porous sintered body;

[0090] Step 5: Post-treatment of Fe-Cu-C-pore gradient porous sintered body

[0091] The mechanical oil is heated to 80°C in a constant temperature water bath and kept warm. The Fe-Cu-C pore gradient porous sintered body obtained in step 4 is immersed in the warm mechanical oil for 6 hours to obtain a Fe-Cu-C lubricating component gradient composite anti-friction material.

[0092] Example 4

[0093] Step 1: Preparation of Cu-coated Fe powder

[0094] A chemical plating solution was prepared with copper sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water in a mass ratio of 1:2.7:0.7:0.002:1.8:50. A constant temperature water bath was used to maintain a constant temperature at 62.5°C and ultrasonic stirring was performed. 1.54 parts by mass of copper sulfate pentahydrate and 1.32 parts by mass of iron powder of copper sulfate pentahydrate were added to the chemical plating solution respectively. A 10 wt % sodium hydroxide solution was continuously added to the chemical plating solution containing the iron powder. The pH value was adjusted to 12.5 and then the plating was stopped. Stop dripping, keep warm and ultrasonically stir for 60 minutes to obtain a solution system containing plated composite powders, wash and replace the supernatant in the solution system with deionized water every 6 hours, dry the obtained composite powder at 85°C for 18 hours to obtain a dry composite powder; reduce the dried composite powder in a hydrogen atmosphere at 350°C for 2.0 hours to obtain composite powders of 1 part by weight of Cu coated with 6.14 parts by weight of Fe and 1 part by weight of Cu coated with 5.25 parts by weight of Fe, respectively;

[0095] Step 2: Preparation of Fe-Cu-C slurries with different compositions

[0096] A bottom layer raw material is prepared by coating 6.14 weight parts of Fe composite powder with 0.7 weight percent graphite powder and 1 weight part of Cu as the balance in a first coating ratio, and a double layer raw material is prepared by coating 5.25 weight parts of Fe composite powder with 0.8 weight percent graphite powder, 6 weight percent pore former soluble starch and 1 weight part of Cu as the balance in a second coating ratio;

[0097] Weigh dispersant triethanolamine, adhesive phenolic resin, plasticizer di(2-ethylhexyl) phthalate, bottom raw material or multilayer raw material and anhydrous ethanol in a mass ratio of 1:2:1:100:100, respectively, ball-mill the bottom raw material and the multilayer raw material at a speed of 400 r / min for 12 h to obtain bottom casting slurry and multilayer casting slurry, respectively, add 2% defoaming agent cyclohexanone and oleic acid (the mass ratio of cyclohexanone to oleic acid is 1:1) to the bottom casting slurry and the multilayer casting slurry, respectively, place in a vacuum environment for defoaming, and obtain bottom Fe-Cu-C slurry and multilayer Fe-Cu-C slurry, respectively;

[0098] Step 3: Preparation of layered composite green body

[0099] The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry were used as raw materials, respectively, by tape casting, drying and curing at 25°C for 48 hours and 36 hours, respectively, to obtain the bottom green body and the multi-layer green body, respectively, and the bottom green body and the multi-layer green body were matched with each other in thickness of 1:0.5, and then subjected to a molding treatment of holding the pressure at a static pressure of 200 MPa for 5 minutes to obtain a layered composite green body;

[0100] Step 4: Preparation of Fe-Cu-C-pore gradient porous sintered body

[0101] The layered composite green body obtained in step 3 is placed in a hydrogen atmosphere, heated to 350°C at a heating rate of 1°C / min, kept warm for 6 hours, and then heated to 520°C at a heating rate of 3°C / min, kept warm for 0.5 hours to obtain a layered composite green body after binder removal treatment; then the layered composite green body after binder removal treatment is placed in a hydrogen atmosphere, heated to 1150°C at a heating rate of 5°C / min, kept warm for 1.0 hours to obtain a Fe-Cu-C-pore gradient porous sintered body;

[0102] Step 5: Post-treatment of Fe-Cu-C-pore gradient porous sintered body

[0103] The solid lubricant polytetrafluoroethylene is heated to 320°C to obtain molten polytetrafluoroethylene, and the Fe-Cu-C-pore gradient porous sintered body is placed in the molten polytetrafluoroethylene for 4 hours of melt immersion treatment, and then cooled to room temperature to obtain a Fe-Cu-C-lubricating component gradient composite anti-friction material.

[0104] Example 5

[0105] Step 1: Preparation of Cu-coated Fe powder

[0106] A chemical plating solution was prepared with cupric sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water in a mass ratio of 1:2.7:0.7:0.002:1.8:50. A constant temperature water bath was used to maintain a constant temperature at 62.5°C and ultrasonic stirring was performed. 1.32 parts by mass of cupric sulfate pentahydrate and 2.25 parts by mass of iron powder were added to the chemical plating solution respectively. A 10 wt % sodium hydroxide solution was continuously added to the chemical plating solution containing the iron powder, and the pH value was adjusted to 12.5. Then, the dropping was stopped, and the solution system containing the plated composite powder was obtained after continuous heat preservation and ultrasonic stirring for 60 minutes. The supernatant in the solution system was washed and replaced with deionized water every 6 hours, and the obtained composite powder was placed at 80° C. for 24 hours to obtain a dry composite powder; the dried composite powder was placed in a hydrogen atmosphere for reduction at 400° C. for 1.5 hours to obtain a composite powder of 1 part by weight of Cu coated with 5.25 parts by weight of Fe and a composite powder of 1 part by weight of Cu coated with 9 parts by weight of Fe, respectively;

[0107] Step 2: Preparation of Fe-Cu-C slurries with different compositions

[0108] A bottom layer material is prepared by coating 5.25 parts by weight of Fe composite powder with 1.0 wt% graphite powder and the balance of 1 part by weight of Cu in a first coating ratio, and a double layer material is prepared by coating 9 parts by weight of Fe composite powder with 0.8 wt% graphite powder, 5 wt% pore-forming agent ammonium bicarbonate powder and the balance of 1 part by weight of Cu in a second coating ratio;

[0109] Weigh dispersant triethanolamine, adhesive phenolic resin, plasticizer dibutyl phthalate, bottom raw material or multi-layer raw material and anhydrous ethanol in a mass ratio of 1:2:1:100:50, ball-mill the bottom raw material and the multi-layer raw material at a speed of 400 r / min for 12 hours to obtain bottom casting slurry and multi-layer casting slurry, respectively, add 1% defoaming agent oleic acid to the bottom casting slurry and the multi-layer casting slurry, respectively, place them in a vacuum environment for defoaming, and obtain bottom Fe-Cu-C slurry and multi-layer Fe-Cu-C slurry, respectively;

[0110] Step 3: Preparation of layered composite green body

[0111] The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry were used as raw materials, respectively, by tape casting, drying and curing at 25°C for 48 hours and 24 hours, respectively, to obtain the bottom green body and the multi-layer green body, respectively, and the bottom green body and the multi-layer green body were matched with each other in thickness of 1:2, and then subjected to a molding treatment of holding the pressure at a static pressure of 200 MPa for 5 minutes to obtain a layered composite green body;

[0112] Step 4: Preparation of Fe-Cu-C-pore gradient porous sintered body

[0113] The layered composite green body obtained in step 3 is placed in a hydrogen atmosphere, heated to 350°C at a heating rate of 1°C / min, kept warm for 5 hours, and heated to 480°C at a heating rate of 3°C / min, kept warm for 1.5 hours to obtain a layered composite green body after binder removal treatment; then the layered composite green body after binder removal treatment is placed in a hydrogen atmosphere, heated to 1080°C at a heating rate of 5°C / min, kept warm for 2.0 hours, and a Fe-Cu-C-pore gradient porous sintered body is obtained;

[0114] Step 5: Post-treatment of Fe-Cu-C-pore gradient porous sintered body

[0115] The solid lubricant polytetrafluoroethylene is heated to 320°C to obtain molten polytetrafluoroethylene, and the Fe-Cu-C-pore gradient porous sintered body is placed in the molten polytetrafluoroethylene for 4 hours of melt immersion treatment, and then cooled to room temperature to obtain a Fe-Cu-C-lubricating component gradient composite anti-friction material.

[0116] Example 6

[0117] The micromorphology of the Fe-Cu-C-lubricating component gradient composite materials prepared in Examples 1-5 was characterized using a Hitachi SU8000 cold field emission scanning electron microscope; the fracture scanning electron microscope (SEM) photo of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared in Example 1 before oil immersion treatment is shown in FIG. Figure 2 ; The cross-sectional scanning electron microscope (SEM) photo of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared in Example 2 before oil immersion treatment is shown in Figure 3 ; The cross-sectional scanning electron microscope (SEM) photo of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared in Example 3 before oil immersion treatment is shown in Figure 4 The fracture scanning electron microscope (SEM) photo of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared in Example 4 before melt immersion treatment is shown in FIG. Figure 5 The friction coefficient of the Fe-Cu-C-lubricating component gradient composite anti-friction materials prepared in Examples 1 to 5 was tested at room temperature using a Zhongke Kaihua HT-1000 friction and wear tester with a load of 10N after a 180-min friction and wear test. The test results are as follows: Figure 6 shown.

[0118] like Figure 2As shown in FIG. 1 , the scanning electron microscope (SEM) photo of the fracture of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared in Example 1 before oil immersion treatment shows that the material is mainly divided into two regions, the bottom layer and the composite layer. Among them, the composite layer has significantly more pores than the bottom layer material due to the addition of pore-forming agent powder.

[0119] like Figure 3 As shown in the cross-sectional scanning electron microscope (SEM) photograph of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared in Example 2 before oil immersion treatment, it can be seen that the material is mainly divided into two layers, namely the bottom layer and the composite layer. At the same time, there is no obvious pore in the bottom layer of the material, which is relatively dense; obvious pores can be seen in the composite layer, and the pore size is less than 500μm.

[0120] like Figure 4 As shown, the cross-sectional scanning electron microscope (SEM) photograph of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared in Example 3 before oil immersion treatment shows that the morphology of the material is similar to that of the composite antifriction material prepared in Example 2 before oil immersion. However, since the pore-forming agent in the multilayer in Example 3 is more than that in the multilayer in Example 2, the number of pores is significantly greater than that in Example 2.

[0121] like Figure 5 As shown, the scanning electron microscope (SEM) photograph of the fracture of the Fe-Cu-C-lubricating component gradient composite antifriction material prepared in Example 4 before melt immersion treatment shows that the fracture morphology is similar to the fracture morphology of the composite antifriction material prepared in Example 1 before oil immersion treatment. The material is mainly divided into two regions, the bottom layer and the composite layer.

[0122] like Figure 6 As shown, the friction coefficient curves of the Fe-Cu-C-lubricating component gradient composite anti-friction materials prepared in Examples 1 to 5 at room temperature with a load of 10N applied can show that the friction coefficient of the alloy after 180 minutes of friction and wear test at room temperature is 0.5-0.8.

[0123] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a Fe-Cu-C-lubricating component gradient composite antifriction material, characterized in that: The method comprises: Step 1: Preparation of Cu-coated Fe powder A chemical plating solution is prepared using copper sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water, and iron powder is plated using the prepared chemical plating solution at a constant temperature of 62.5°C, and the plated composite powder is reduced to obtain Cu-coated Fe composite powders with different coating ratios; Step 2: Preparation of Fe-Cu-C slurries with different compositions A first coating ratio of Cu-coated Fe composite powder and graphite powder are used to prepare a base material, and a second coating ratio of Cu-coated Fe composite powder, graphite powder and a pore-forming agent are used to prepare a composite material. The bottom layer raw material and the multi-layer raw material are respectively subjected to ball milling treatment to obtain a bottom layer tape casting slurry and a multi-layer tape casting slurry, respectively; the bottom layer tape casting slurry and the multi-layer tape casting slurry are respectively subjected to vacuum defoaming treatment to obtain a bottom layer Fe-Cu-C slurry and a multi-layer Fe-Cu-C slurry; Step 3: Preparation of layered composite green body The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry are used as raw materials respectively, and the bottom green body and the multi-layer green body are obtained by casting, drying and curing. After the bottom green body and the multi-layer green body are matched, a layered composite green body is obtained by molding. Step 4: Preparation of Fe-Cu-C-pore gradient porous sintered body The layered composite green body obtained in step 3 is subjected to a binder removal treatment in a hydrogen atmosphere, and is pressurelessly sintered in a hydrogen atmosphere to obtain a Fe-Cu-C-pore gradient porous sintered body; Step 5: Post-treatment of Fe-Cu-C-pore gradient porous sintered body The Fe-Cu-C-pore gradient porous sintered body obtained in step 4 is subjected to oil immersion treatment or melt-immersion solid lubricant treatment to obtain a Fe-Cu-C-lubricating component gradient composite anti-friction material.

2. The method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material according to claim 1, characterized in that: Step one includes: A chemical plating solution is prepared by using copper sulfate pentahydrate, disodium ethylenediaminetetraacetic acid, solid sodium hydroxide, dipyridine, formaldehyde and deionized water in a mass ratio of 1:2.7:0.7:0.002:1.8:50; A constant temperature water bath is used to keep a certain mass of chemical plating solution at 62.5° C. and ultrasonically stir it, and iron powder is added to the chemical plating solution, wherein the mass ratio of copper sulfate pentahydrate to iron powder in the chemical plating solution is 1:1-1:2.25, and a 10wt% sodium hydroxide solution is added dropwise to the chemical plating solution containing the iron powder, and the pH value is adjusted to 12.5 and then the addition is stopped, and the temperature is kept and ultrasonically stirred for 60 minutes, and the supernatant in the solution system is washed and replaced with deionized water every 6 hours, and the obtained composite powder is placed at 80-90° C. and dried for 12-24 hours to obtain a dry composite powder; The dried composite powder is placed in a hydrogen atmosphere at 300-400° C. for reduction for 1-2 hours to obtain Cu-coated Fe composite powders with different coating ratios.

3. The method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material according to claim 1, characterized in that: Step 2 includes: A base material is prepared by using a Cu-coated Fe composite powder and graphite powder in a first coating ratio, wherein the content of the graphite powder is 0.6-1.0wt%, and the mass ratio of Cu to Fe in the Cu-coated Fe composite powder in the first coating ratio is 1:5.25 to 1:9; A composite raw material is prepared by using a Cu-coated Fe composite powder, graphite powder and a pore former in a second coating ratio, wherein the content of the graphite powder is 0.6-1.0wt%, the content of the pore former is 5-10wt%, the mass ratio of Cu to Fe in the Cu-coated Fe composite powder in the second coating ratio is 1:4 to 1:9, and the pore former powder is ammonium bicarbonate or soluble starch or a mixture of ammonium bicarbonate and soluble starch in equal proportions; The bottom layer raw material and the multi-layer raw material are respectively subjected to ball milling treatment to obtain a bottom layer casting slurry and a multi-layer casting slurry, and the obtained bottom layer casting slurry and the multi-layer casting slurry are respectively subjected to vacuum defoaming treatment to obtain a bottom layer Fe-Cu-C slurry and a multi-layer Fe-Cu-C slurry.

4. The method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material according to claim 3, characterized in that: In step 2, the bottom layer raw material and the multi-layer raw material are respectively subjected to ball milling treatment to obtain a bottom layer casting slurry and a multi-layer casting slurry, respectively, and the obtained bottom layer casting slurry and the multi-layer casting slurry are respectively subjected to vacuum defoaming treatment, including: The bottom raw material and the multi-layer raw material are respectively ball-milled at a speed of 400 r / min for 6-18 hours using a dispersant, a binder, a plasticizer and anhydrous ethanol as ball milling auxiliary materials to obtain a bottom casting slurry and a multi-layer casting slurry, wherein the mass ratio of the dispersant, the binder, the plasticizer to the bottom raw material or the multi-layer raw material is 1:2:1:100, and the mass ratio of the anhydrous ethanol to the bottom raw material or the multi-layer raw material is 1:1 to 1:2; Defoaming agents were added to the bottom casting slurry and the multi-layer casting slurry respectively, and the slurries were placed in a vacuum environment for defoaming to obtain Fe-Cu-C slurries with different compositions, wherein the mass ratio of the total mass of the defoaming agent to the bottom raw material or the multi-layer raw material was 1:100 to 1:

50.

5. The method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material according to claim 4, characterized in that: In step 2, the dispersant is polyethylene glycol or triethanolamine, the binder is polyvinyl butyral or phenolic resin, the plasticizer is phthalates or dibutyl phthalate, and the defoamer is one or more of cyclohexanone, dimethyl silicone oil or oleic acid. When the defoamer is composed of two or more of cyclohexanone, dimethyl silicone oil or oleic acid, the components of the defoamer are mixed in equal proportions.

6. The method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material according to claim 1, characterized in that: Step three includes: The bottom Fe-Cu-C slurry and the multi-layer Fe-Cu-C slurry are used as raw materials respectively, and the bottom green body and the multi-layer green body are obtained respectively by tape casting and drying and solidification treatment, wherein the drying and solidification treatment temperature is 25-30° C. and the drying and solidification time is 24-48 hours; After matching the bottom green body and the multi-layer green body, the green body is kept under a static pressure of 200 MPa for 5 minutes to obtain a layered composite green body, wherein the thickness of the matched bottom green body and the multi-layer green body is 1:0.5 to 1:

2.

7. The method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material according to claim 1, characterized in that: Step 4 includes: The layered composite green body obtained in step 3 is placed in a hydrogen atmosphere, heated to 300-350°C at a heating rate of 1°C / min, and kept warm for 5-7h, and then heated to 480-520°C at a heating rate of 3°C / min, and kept warm for 0.5-1.5h, to obtain a layered composite green body after binder removal treatment; The debinding-treated layered composite green body is placed in a hydrogen atmosphere, heated to 1080-1180°C at a heating rate of 5°C / min, and kept warm for 1-2 hours to obtain a Fe-Cu-C-pore gradient porous sintered body.

8. The method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material according to claim 1, characterized in that: In step five, the oil immersion treatment includes: heating the mechanical oil to 80-90° C. in a constant temperature water bath and immersing the Fe-Cu-C-pore gradient porous sintered body in the thermally-insulated mechanical oil for 2-6 hours.

9. The method for preparing the Fe-Cu-C-lubricating component gradient composite antifriction material according to claim 1, characterized in that: In step five, the solid lubricant infiltration treatment includes: heating the solid lubricant polytetrafluoroethylene to 320-340°C to obtain molten polytetrafluoroethylene, placing the Fe-Cu-C-pore gradient porous sintered body in the molten polytetrafluoroethylene for infiltration treatment for 2-4 hours, and cooling to room temperature.

10. A Fe-Cu-C-lubricating component gradient composite anti-friction material, characterized in that: The Fe-Cu-C-lubricating component gradient composite anti-friction material is prepared according to any one of the methods described in claims 1-9.

Citation Information

Patent Citations

  • Functionally-graded wear-resistant iron-based composite material and preparation method thereof

    CN105817605A

  • Ferrum-based powder metallurgy antifriction material and preparation method thereof

    CN104384502A

  • High-strength antifriction double-layered iron base powder metallurgy material and preparation method thereof

    CN106041099A